Intron 4 VNTR Polymorphism of eNOS Gene Is Protective for Cardiac Syndrome X. (1st January 2010) - Sinici, Incilay; Atalar, Enver; Kepez, Alper; Hayran, Mutlu; Aksoyek, Serdar; Tokgozoglu, Lale; Ozmen, Ferhan
Abstract : Microvascular abnormalities caused by endothelial dysfunction seem to be responsible for the myocardial ischemia in patients with cardiac syndrome X (CSX). Nitric oxide is a key mediator of endothelial function and is synthesized by endothelial nitric oxide synthase (eNOS). We investigated if the 3 potential polymorphisms of the eNOS gene (VNTR in intron 4, T786C polymorphism in the promoter region, and G894T polymorphism in exon 7) are independent risk factors for CSX. Sixty-nine patients with CSX and 73 healthy controls were studied. Genotypes were determined through polymerase chain reaction with or without restriction endonuclease digestions. Genotype distribution was significantly different between patients with CSX and controls for intron 4aa (allele for 4 repeats of 27 bp), intron 4aa genotype frequency being 3.2% and 6.8%, respectively. The presence of intron 4a is 3.2 (odds ratio) times protective (95% confidence interval, 1.5-6.8) for the risk of CSX disease. The protective effect of intron 4a polymorphism also holds after adjustment for age and sex and when the study group is limited to those without hypertension and hyperlipidemia. No significant difference was observed in genotype distribution of G894T and T786C polymorphism between patients with CSX and controls. In conclusion, intron 4aa genotype of eNOS gene is protective for CSX. No association was found between promoter and exon 7 polymorphisms of eNOS gene and CSX.